The correlation between family empowerment and the role of family health tasks in preventing anemia during pregnancy - Triharini, Mira; Wahyuni, Sylvia Dwi; Armini, Ni Ketut Alit; Ulfiana, Elida; Lailiyaturrohmah, Zurinda Dwi Nur; Ramadhani, Ananda Amalia (International Journal of Public Health Science (IJPHS), 2025)
Anemia in pregnancy can harm the mother and baby. Prevention of anemia in pregnant women cannot be separated from the role of the family. Increasing the role of the family requires family empowerment, especially from the husband. This study aimed to analyze the correlation between family empowerment and family role in preventing anemia during pregnancy. This study used a descriptive correlational approach. Sample was 150 of pregnant women who received antenatal care at the Klampis Ngasem and Pacar Keling Health Center, East Java, Indonesia, and were selected using a consecutive sampling method. A statistical test to examine the relationship between independent and dependent variables is conducted using Spearman's Rho. and Chi-square. This study indicates a significant correlation between family empowerment and family role in prevention anemia during pregnancy (p = 0.000; r = 0.578). There is a relationship between the components of family empowerment and family function. Motivation (p = 0.000; r = 0.643), cognitive (p = 0.000; r = 0.552), and personal traits (p = 0.000; r = 0.565) correlated with family role in preventing anemia during pregnancy. Health workers need to provide education to increase family empowerment to increase the role of the family in the five family tasks in preventing anemia during pregnancy.